Planetary Astrobiology - Marais, David J.; Schmidt, Britney E.; Arney, Giada Nicole; Meadows, Victoria S. (University of Arizona space science series., 2020)
"Planetary Astrobiology provides an accessible, interdisciplinary gateway to the frontiers of knowledge in astrobiology via results from the exploration of our own solar system and exoplanetary systems"--